Field Experiments and a Meta‐Analysis Reveal a Minor Influence of Nitrogen Addition on Phosphorus Fractions in Forests - Qingshui Yu; Xiaofeng Ni; Frank Hagedorn; Josep Penuelas; Jordi Sardans; Mai‐He Li; Suhui Ma; Jianxiao Zhu; Di Tian; Chengyang Zheng; Jiangling Zhu; Chengjun Ji; et al. (Global Change Biology, 2025)
Anthropogenic nitrogen (N) inputs can significantly impact nutrient cycling and ecosystem functioning in terrestrial ecosystems. However, the effects of N addition on phosphorus (P) cycling processes in forest ecosystems remain unclear. In this study, we combined data from a long‐term (11‐year) N addition experiment across seven different forests ranging from temperate to tropical biomes, with a global meta‐analysis from 88 relevant publications, to investigate the responses of P cycling‐related variables to N inputs in forest ecosystems. We found that N addition had little effect on most P cycling‐related variables (e.g., leaf P, soil total P, soil available P, soil P fractions, and microbial biomass P) across the studied forest ecosystems. The meta‐analysis highlighted that N‐induced changes in P cycling were highly variable. Only a few variables, such as the leaf P concentration and the activity of soil acid phosphatase, presented significant responses to N addition and changed with climatic zone and the amount and duration of N inputs. Our study suggests that P cycling processes in forest ecosystems remain largely unaffected by N inputs. Our findings contribute to a better understanding and prediction of biogeochemical cycles in the context of N deposition related to anthropogenic activities and global climate change.